Between Two Worlds: Romania and India. Essays on Expanding Borders through Culture - GLIGOR, Mihaela; GHOSH, Lipi (2023)
The cultural relations between India and Romania are interesting to study and to understand. India is a country of immense diversity, of extraordinary customs, and a genuine feast of opinions, which attracts researchers from all over the world. Romanians are people with a profound sensibility. The two cultures met on the common ground of spirituality and the results are remarkable, as it is shown in this special volume.